Bacillary Dysentery in Children Below Five Years of Age at the General Hospital, Manado - T. H. Rampengan; A. S. Ongkie; J. M. Wantania; Muzief Munir (Paediatrica Indonesiana, 1982)
Forty-six children below five years of age, diagnosed as having BacillaryDysentery, were admitted to the Department of Child Health, Medical School,University of Sam RatuiangifGunung Wenang General Hospital, Manado, during the period from July 1974 through June 1976. The majority of cases (89.2%) were below two years old, the youngest being 5 days of age. The main complaints when hospitalized were diarrhea (91.3%) and fever (76.1%).For treatment, rehydration and a combinartion of Tetracycline and Kanainycinwere used. The average length of hospitalization was 8.7 days. All of thepatients recovered.